Revitalizing Malaysia's agro sector: cultivating a path to food security - Razali, Hazlina; Ali Kutty, Mohamad Fahmi; Shaiful Fairuz, Nur Fatin Syakirah; Abdul Ghani, Abdul Azim; Puteh, Fadilah (Faculty of Administrative Science and Policy Studies, 2025)
Malaysia's agricultural sector is crucial for ensuring food security and promoting economic growth. Since the 2008 global financial crisis, food security has become a top priority on the national agenda. Every country, including Malaysia, worries about food security. Despite the country's inability to produce food independently, food is available throughout the year. Malaysia outsources its food supply to satisfy local consumer demand, making it a net importer of food. This situation is deemed necessary due to the country's limited arable land and farmers' restricted output capabilities. This article primarily focused on the Malaysian Ministry of Agriculture and Food Security (MAFS) in its efforts to rejuvenate the agro sector and enhance food security. Malaysia's rejuvenate the agro sector and food security were analysed using some key strategic management techniques, including PEST analysis, a custom-mad internal analysis, and SWOT analysis. These approaches serves as a tool for identifying food security issues. The TOWS matrix and BOS were then employed to generate many viable recommendations. This article provides information on food security in Malaysia as well as appropriate recommendations for stakeholders.